Caregiver acceptability of seasonal malaria chemoprevention in two districts in the Upper West region, Ghana: a cross-sectional study - Youssouf Diarra; Michael M. Opoku; Charles E. Amankwa; Raymond B. Annor; Justice Nonvignon; Harriet A. Bonful (Malaria Journal)
Abstract Background Acceptability of malaria chemoprevention interventions by caregivers is crucial for overall programme success. This study assessed coverage and acceptability of Seasonal Malaria Chemoprevention (SMC) in selected communities in the Northern part of Ghana. Methods An analytical cross-sectional design was conducted from “July 23rd to August 4th, 2020—a 12-day period that covered 5 days of the first SMC implementation cycle and 7 days post-implementation. Using a stratified multi-stage sampling technique, a total of 495 caregivers providing care for 569 eligible children aged 3–59 months from randomly selected households in the study communities were enrolled into the study. Acceptability of SMC was assessed on a set of 19 questionnaire items-8 of the items measured caregivers’ perceptions and 11 items measured children’s reaction to administered medicines. Univariable and stepwise multivariable logistic regression analyses were performed to assess the predictors of acceptability of SMC at a 95% confidence interval and a p-value of 0.05. Results SMC coverage was 95.1% (541/569). Caregivers had a good level of knowledge of SMC (n = 475; 96.0%; 95% CI 94.2—97.7%) and a good perception of SMC (n = 471; 95.2%; 95% CI 93.3–97.0). Seven out of ten caregivers (70.9%; 95% CI 66.9–74.9%) had good acceptability of SMC. For 7 out of 28 children who did not receive the SMC intervention, their caregivers intentionally refused them the intervention. Of those that received the treatment, 17.2% (n = 85; 95%CI 13.8–20.5%) of caregivers had at least one leftover amodiaquine tablet after the third day of treatment. Caregivers who practice Christianity or Islam had better acceptability than caregivers who practice African traditional religion (p < 0.001). Conclusion Health authorities and stakeholders can work towards bridging the gap between knowledge and SMC treatment practices of caregivers through continuous education, adherence counseling, and effective monitoring of SMC practices in malaria-endemic countries.